(3cJGH GdCQHYjf aj EQTGO GdSGFQjf Edi efGRd GdeJajfs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf Hf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg GeG HYO abO Qhi Yf GdfHi Udi Gddg Ydjg hBdg hSde HWQb TJG hQhGjGJ eNJdaI Gfg bGd (B:" (3ef MaX Ydi GeJi GQHYjf MOjKkG ef GdSfI cfJ dg TajYkG jhe GdbjGeI(B" s
(3BNQgG (B:s
(3PcQJc dG Cfi CfSGc deMg hGjSQ eG ai GdPcQ PcQ dSGfi aEf SCd GdhGThf aje SdhJgG abd faS MQ SdjJ aJSdJ JeJ GdGQHYhf HMeO Gddg JYGdi hMSf Jhajbg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQM hGedGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B58s
Keywords: (3GdMOjK h GdeUWdMs